Host-parasite life-histories of the diurnal vs. nocturnal chronotypes of Schistosoma mansoni: adaptive significance - Mouahid, Gabriel; Nguema, Rodrigue Mintsa; Al Mashikhi, Khalid M.; Al Yafae, Salem A.; Idris, Mohamed A.; Mone, Helene (Tropical Medicine & International Health, 2019)
Objectives To optimise host-to-host transmission, digenean trematodes (parasites) synchronise their cercarial emission patterns with the aquatic activities of their vertebrate hosts. Schistosoma mansoni has two different circadian chronotypes: a diurnal shedding pattern with a mean peak occurring at 11:00 h, and a nocturnal shedding pattern with a mean peak occurring at 20:00 h. We analysed the life-history variations between these two chronotypes at the levels of the parasite and its hosts. Methods For each chronotype, we quantified three life-history traits related to the parasite (prepatent period, infection rate and cercarial production) and analysed the morphometry and the morphology of the parasite eggs; we also quantified three life-history traits related to the snail intermediate host (shell diameter, fecundity and survival rate) and one life-history trait related to the experimental definitive host (survival rate). A phylogeny based on the mitochondrial cytochrome-oxidase gene was made on samples of both chronotypes. Results Life-history analysis revealed significant variations between the two chronotypes. Life-history traits were optimal for both the parasite and the snail host for the diurnal chronotype compared to the nocturnal one. The new chronotype behaved like an allopatric population towards its snail host. Phylogenetic analysis supports the hypothesis of a lateral transfer of S. mansoni from humans to Rattus rattus. These results were interpreted in terms of an ongoing sympatric speciation. Conclusion The nocturnal chronotype of S. mansoni showed non-adapted life-history traits in its relation with the snail intermediate host Biomphalaria pfeifferi. The emergence of this new phenotype is probably linked to divergent natural selection.